IMPLEMENTATION OF THE BRIN ARCHIVES CLASSIFICATION POLICY AND ITS IMPACT ON RESEARCH ARCHIVES ACCESSIBILITY - Firnalia, Firnalia; Nurdin , Nurliah; Istania, Ratri (DIA: Jurnal Administrasi Publik, 2026)
This study analyzes the implementation of the Archives Classification Policy based on the Surat Keputusan Kepala BRIN Nomor 224 Tahun 2022 at the National Research and Innovation Agency (BRIN) and its impact on the accessibility of research archives. Using a qualitative approach through field studies, data was collected through in-depth interviews, observations, and document reviews, then analyzed using Janowski’s Digital Government model (encompassing digitization, transformation, engagement, and contextualization) along with a SWOT analysis. The research findings indicate that policy implementation has not been fully effective. The main challenges are multidimensional, including: (1) Digitalization Stage: low human resource readiness in digital literacy and metadata management, despite the availability of technological infrastructure; (2) Transformation Stage: resistance in work culture and weak discipline and personal accountability related to archiving; (3) Engagement Stage: top-down dissemination with minimal active employee participation; and (4) Contextualization Stage: classification policies that are too rigid and do not accommodate the diversity of research fields. This condition directly hinders the accessibility of research archives, impacting research efficiency, institutional transparency, and potentially leading to the loss of national knowledge assets. Based on a SWOT analysis, this study formulates a holistic and synergistic optimization strategy, including: (1) Technology-Based Strategy: integration of the SINAR-TNDE-SRIKANDI system, implementation of AI-based automatic classification, and development of an open metadata portal; (2) People-Based Strategy: tiered training programs, formation of digital champions, and a reward and punishment system; and (3) Policy-Based Strategy: development of function-based classification, standardization of access procedures, and integration of archives management into the research cycle. This recommended implementation model is expected to create an effective, adaptive, and sustainable digital archiving system at BRIN, thereby supporting transparent and accountable national scientific knowledge governance.